1988
DOI: 10.1007/bf00404109
|View full text |Cite
|
Sign up to set email alerts
|

The sonographic signs of the peritoneal pseudocyst obstructing the ventriculo-peritoneal shunt in children

Abstract: The installation of the ventriculo-peritoneal shunt (VPS) is on the rise in the pediatric age. Its obstruction is a major cause for further deterioration of the already present hydrocephalus. Distal VPS obstruction may be due to a pseudocyst, an infected pseudocyst or an abscess-formation within the peritoneal cavity. These pathologies are identified through an abdominal radiograph and ultrasonography. The sonographic signs are described and its differential diagnosis is discussed in relation to 6 diagnosed ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…[28] Sonographic signs include a sonolucent mass with/without septations, the so-called railroad sign and a fluid-echo line. [17] More commonly, it can be visualized as a smooth pseudomembrane echo-free fluid collection. [28] CT, while considered as definitive as ultrasound,[11] is more costly, and offers radiation exposure.…”
Section: Discussionmentioning
confidence: 99%
“…[28] Sonographic signs include a sonolucent mass with/without septations, the so-called railroad sign and a fluid-echo line. [17] More commonly, it can be visualized as a smooth pseudomembrane echo-free fluid collection. [28] CT, while considered as definitive as ultrasound,[11] is more costly, and offers radiation exposure.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to identify the shunt tip within the pseudocyst, and the hyperechoic tip must be differentiated from septa 9 . The shunt tip will produce an echo signal of higher amplitude than a septum, and the two parallel sides of the shunt produce the characteristic ‘railroad sign’ 8 . Visualizing the shunt tip within the cyst also helps distinguish a CSF pseudocyst from pancreatic pseudocyst or ovarian cystadenoma 9 .…”
Section: Discussionmentioning
confidence: 99%
“…7 It has been suggested that smaller pseudocysts tend to be infected, and larger pseudocysts tend to be sterile, 5 Ultrasound shows a well-defined sonolucent mass, with posterior acoustic enhancement. A non-infected cyst will show uniform echotexture within, 8 whereas septa may occur in an infected pseudocyst, which often has internal echoes or a fluid level. 8,9 It is important to identify the shunt tip within the pseudocyst, and the hyperechoic tip must be differentiated from septa.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations